Population health management at Atrius Health - Licholai, Greg; Berke, Aron; Elias, Jaan (London : Yale School of Management, 2016)
In mid-2015, Emily Brower was appointed to the newly-created position of Vice President of Population Health at Atrius Health. Brower faced the challenge of framing a strategic plan to integrate population health approaches more broadly across the large physician practice organization.In healthcare services, population health management refers to developing systems of care for groups of patients based on their clinical needs to increase quality, control costs, and enhance patient experience. One of the central ideas of population health is to use medical informatics to manage the care of groups of patients who shared demographic characteristics or chronic ailments. In so doing, population health changed the focus from treating individuals to managing larger groups of patients.Brower faced numerous design decisions in creating a strategy to realize the full promise of population health within Atrius Health. How should Atrius Health most effectively define the populations to be managed? Should the services be located within the local practice offices or managed centrally? How should physicians be involved in the implementation of the programs?
Originally Published InLicholai, G., Berke, A., & Elias, J. (2016). Population health management at Atrius Health. 16-015. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Brower, Emily; Atrius Health; Health planning; Health services administration; Managed care plans (Medical care); Health services accessibility